Estimating the prevalence of alcohol-related disorders and treatment utilization in Bremen 2016/2017 through routine data linkage - Möckl, Justin; Lindemann, Christina; Manthey, Jakob; Schulte, Bernd; Reimer, Jens; Pogarell, Oliver; Kraus, Ludwig (Frontiers in Psychiatry, 2023)
Background: In Germany, most individuals with alcohol dependence are recognized by the health care system and about 16% per year receive addiction-specific care. This paper aimed to analyze the prevalence and treatment utilization rate of people with alcohol dependence by type of addiction-specific care in the federal state of Bremen using routine data. Methods: The number of individuals with alcohol dependence was estimated using data from the 2018 Epidemiological Survey of Substance Abuse. Linked routine data of two statutory health insurances (SHIs), the German Pension Insurance (GPI) and the communal hospital group Gesundheit Nord (GeNo), from 2016/2017, were analyzed. Based on SHI data, the administrative prevalence of various alcohol-related diagnoses according to the International Classification of Diseases (ICD-10), in various treatment settings, was extrapolated to the total population of Bremen. Based on all routine data sources, treatment and care services for individuals with alcohol dependence were also extrapolated to Bremen’s total population. Care services included outpatient addiction care visits and addiction-specific treatments, (i.e., qualified withdrawal treatment (QWT), outpatient pharmacotherapy as relapse prevention, and rehabilitation treatment). Results: Of the estimated 15,792 individuals with alcohol dependence in Bremen, 72.4% (n=11,427) had a diagnosis documented with an ICD-10 code for alcohol dependence (F10.2) or withdrawal symptoms (F10.3-F10.4) and 10.0% (n=1,577) used one or more addiction-specific care services during the observation period. More specifically, 3.7% (n=675) received outpatient addiction care, 3.9% (n=736) initiated QWT, 0.8% (n=133) received pharmacotherapy, and 2.6% (n=405) underwent rehabilitation treatment. The share of seeking addiction-specific treatment after diagnosis was highest among younger and male patients. Conclusion: Although most individuals with alcohol dependence are documented in the health system, utilization rates of addiction-specific treatments are low. These low utilization rates suggest that there are existing barriers to transferring patients with alcohol dependence into addiction-specific care. Strengthening primary medical care provision in dealing with alcohol-related disorders and improving networking within the addiction support system appear to be particularly appropriate.